The Influence of Leadership and Teamwork on Employee Performance with Organizational Commitment as a Mediating Variable at PT. Primayudha Mandirijaya - Rizky Marsha Febriyanti; Jati Waskito (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to analyze the effect of Leadership and Teamwork on Employee Performance with Organizational Commitment as a mediator. The type of research used is quantitative research with a questionnaire distribution method through a questionnaire. The population of this study were all employees of PT Primayudha Mandirijaya. The sample used in this study amounted to one hundred and sixty respondents. The sampling technique in this study was using a non-probability sampling technique using purposive sampling. Data were analyzed using SmartPLS 3.0. There is a positive and significant influence between Leadership on Employee Performance at PT Primayudha Mandirijaya (H1). There is a positive and significant influence between Teamwork on Employee Performance at PT Primayudha Mandirijaya (H2) There is a positive and significant influence between Leadership on Organizational Commitment at PT Primayudha Mandirijaya (H3) There is a positive and significant influence between Teamwork on Organizational Commitment at PT. Primayudha Mandirijaya (H4) There is a positive and significant influence between Leadership on Employee Performance of PT. Primayudha Mandirijaya through Organizational Commitment as a mediating variable (H5) There is no positive and significant influence between Teamwork on Employee Performance of PT. Primayudha Mandirijaya through Organizational Commitment as a mediating variable (H6).